Asymmetric brain atrophy in Huntington's disease: A postmortem MRI study - Lila, Eardi; Hunt, David; Child, Daniel D; Latimer, Caitlin; Le, Bianca; Davis, Marie; Jayadev, Suman; Bird, Thomas D; Shojaie, Ali; Mac Donald, Christine L (Journal of Huntington's disease, 2025)
Background Huntington's disease is a progressive, autosomal dominant, neurodegenerative disease caused by a CAG repeat expansion in the HTT gene. Medium spiny neurons of the striatum are especially vulnerable to the disease, and atrophy of the caudate and putamen can be documented by neuroimaging years before the onset of symptoms. Objective In this study, we aimed to characterize region-specific gray and white matter differences between Huntington's disease patients and controls. Methods We conducted a postmortem MRI study of the brains of 15 adults diagnosed with symptomatic Huntington's disease and 26 control subjects, aiming to compare the differences in regional grey and white matter volumes between the two groups. Results The study revealed decreased volumes in both grey and white matter in patients with Huntington's disease, with the largest effect sizes observed in caudate and putamen. Notably, the atrophy predominantly affected the left hemisphere, particularly impacting grey and white matter regions adjacent to the pars opercularis, precentral, supramarginal, and pars orbitalis gyri, and the lateral orbitofrontal cortex. In the control group, asymmetry stems from larger left hemisphere regions compared to right, whereas an opposite pattern is observed in the Huntington's disease group. Conclusions These results suggest progressive, diffuse, and asymmetric grey and white matter atrophy occurs in Huntington's disease. The reasons for this asymmetry remain unknown; however, our study provides a more detailed characterization of previously reported grey and white matter changes in Huntington's disease, as observed through postmortem histopathological and MRI studies.